2020
DOI: 10.4103/jfmpc.jfmpc_1008_19
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of nurses within a nurse-led multidisciplinary approach in providing care for patients with diabetic foot ulcer

Abstract: Background and Aims: Diabetic foot ulcers require special attention due to their complex and chronic nature and special care and the Nurse-led approach has emerged in the current situation in response to the increasing need for health care as a way to treat chronic patients and provide them with ongoing care. Providing this specialized duty in nursing can be promoted and enhanced the professional independence of nurses and presents challenges. This study has been conducted to make an understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Despite the reported usefulness and effectiveness of nurse-led diabetes care (Guest et al, 2017 ), the literature also reported controversial views related to the acceptability of nurse-led care (Guest et al, 2017 ). A recent qualitative study experiences about a nurse-led multidisciplinary team of diabetic foot ulcer care highlighted the importance of a nurse-led interdisciplinary role within the multidisciplinary team (Nayeri et al, 2020 ). Favouring the multidisciplinary team was attributed to ensuring that complex wounds are adequately treated (Nayeri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the reported usefulness and effectiveness of nurse-led diabetes care (Guest et al, 2017 ), the literature also reported controversial views related to the acceptability of nurse-led care (Guest et al, 2017 ). A recent qualitative study experiences about a nurse-led multidisciplinary team of diabetic foot ulcer care highlighted the importance of a nurse-led interdisciplinary role within the multidisciplinary team (Nayeri et al, 2020 ). Favouring the multidisciplinary team was attributed to ensuring that complex wounds are adequately treated (Nayeri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study experiences about a nurse-led multidisciplinary team of diabetic foot ulcer care highlighted the importance of a nurse-led interdisciplinary role within the multidisciplinary team (Nayeri et al, 2020 ). Favouring the multidisciplinary team was attributed to ensuring that complex wounds are adequately treated (Nayeri et al, 2020 ). An international meta-analysis on the effect of nurse-led randomized control trials on cardiovascular risk factors and HbA1c in diabetes patients found that most nurse-led interventions were implemented with physicians mainly as supervisors (Daly et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support the implementation of integrated foot care programs, it is essential to focus on training and capacity‐building for health care professionals. Providing specialized training to primary care physicians, nurses, and other health care providers in DFU management has been shown to improve their knowledge and skills in wound care, reducing the burden on specialized care 40 . LMICs can develop a strong workforce capable of addressing the growing DFU burden by improving the skills and expertize of health care professionals.…”
Section: Importance Of Early Intervention and Adequate Care Of Dfu; E...mentioning
confidence: 99%
“…The education could be provided through continuing training in the workplace (Beuscher et al, 2019) or by developing foot health-related courses for nursing education curricula. Caring for foot problems in older people with long-term health problems requires interprofessional collaboration (Nayeri et al, 2020), therefore nurses in older people care need also know when older individuals' foot problems need consultation from physician, podiatrist or orthotic specialist. The ultimate aim of the foot care is to maintain mobility among older individuals mobile and assure their independence in daily activities (James et al, 2021).…”
Section: Ta B L Ementioning
confidence: 99%